Government Regulation, Technology and Development of SME-s - Koti, Sorina; Dr. Klaudeta Merollari (European Journal of Multidisciplinary Studies, 2016)
The aim of the paper is to analyze the factors that determine business growth and the impact on the GDP of the country. The paper analyses Albania, as one of the countries in the South East Europe. Albania is still passing through a transition period at all levels, economic and political. Albania has made serious steps in the development of the state of law, of the financial system and it is working on the achievements of goals, such as: becoming an EU member, stabilization of the fiscal and monetary policies, stability of prices, fighting against corruption, incentives for private investments, reduction of business’s taxes etc. The achievement of these goals will bring more motivation and incentives for growth, an increase in domestic and foreign direct investments. The government of Albania is still working on the future strategies that will bring Albania near to the European countries. The partial achievement of the above goals has created a positive environment, but still there is enough room for change and stabilization. The Albanian governments have improved the business climate, in order to create easier methods in the way of doing business, by attracting more foreign investors and creating a positive climate. Albania has experienced an increase of interest from foreign companies, which have invested in the main fields of economic such as: banking, energy, telecommunication, gas-oil, supermarkets, construction etc. However, some fiscal policies have changed during the last three years, which has caused a tightening of credit, investment, growth and income. Nowadays, Albania is not in a good position compare to neighborhood countries and it is facing recession problems that need immediate solution to overcome the crisis.